p97/VCP- and Lys48-linked polyubiquitination form a new signaling pathway in DNA damage response - Ramadan, Kristijan (Cell cycle (Georgetown, Tex.), 2012)
RNF8/RNF168-dependent Lys63-linked polyubiquitination at sites of DNA double-strand breaks (DSBs) was originally regarded as the sole ubiquitin-signaling pathway involved in the DNA damage response (DDR). However, ubiquitin-dependent p97/VCP segregase activity and RNF8-dependent Lys48-linked polyubiquitin chains at DSB sites have recently been identified as components of an additional and parallel ubiquitin-signaling DDR pathway. This newly identified pathway is essential to spatiotemporal protein turnover and regulates both main branches of DSB repair, homologous recombination and nonhomologous end joining. In this report, the function of the RNF8/Lys48 polyubiquitin chains/p97 pathway is discussed in the context of DSB repair and p97 chromatin-related functions.